Bearing Capacity Calculation of Soft Foundation of Waste Dumps—A Case of Open-Pit Mine - Jiang, Juyu; Yang, Huiwen; Cao, Lanzhu; Wang, Dong; Wang, Laigui; Jia, Zhengzhao; Lu, Ye; Di, Shuai (Frontiers in Earth Science, 2022)
For a waste dump with soft foundation, the foundation bearing capacity has an important impact on the slope stability. According to the load distribution and stress characteristics of a waste dump, combined the gravity load of the triangular slope of the waste dump and the passive earth pressure exerted by the foun-dation soil with an improved Plandtl formula, the foundation bearing capacity and the ultimate pile height of a waste dump are calculated and determined. The concept of foundation bearing capacity of a waste dump is redefined, that is, the ultimate pile height corresponding to a certain slope angle. A method for determining the ultimate pile height of a waste dump based on the slope angle of the waste dump is proposed, and the relation function between dump slope angle and waste height is established. The results show that the sliding moment increment (∆MS) caused by the gravity load of the triangular slope after waste increasing is positively proportional to the pile height increment (∆H); the anti-sliding moment increment (∆MAS) is positively proportional to or positively correlated with the pile height increment (∆H); the slope angle of the waste dump decreases with the increase of the thickness of soft bedrocks and smaller thickness of soft bedrocks is more favorable to the ultimate pile height of the waste dump. The research results can provide reference for the calculation of the bearing capacity of soft foundation and the optimal design of slope shape of waste dumps.